Evaluation of neotectonic variability along major Himalayan thrusts within the Kali River basin using geomorphic markers, Central Kumaun Himalaya, India. (11th February 2019) - Talukdar, Riyanka; Kothyari, Girish Ch.; Pant, Charu C.
Abstract : We have analysed the geomorphic signatures in aggregation with the geomorphic indices with respect to hinterland and foreland neotectonic variability across the major Himalayan thrust system along the Kali River valley of eastern Kumaun Himalaya. The valley floor morphology in the vicinity of the major thrust gave rise to the accommodation space for the aggradation of the recent fluvial sediments. For a longitudinal distance of 212 km between the South Tibet Detachment (STD) and Himalayan Frontal Thrust (HFT), the valley has preserved significant aggradational landforms. These landforms have been physically examined to explain the spatial and temporal variability in phases of aggradation/incision in response to the tectonic activity during the late Quaternary. Fossil valleys and associated epigenetic gorges, cut‐and‐fill terraces with thick alluvial cover, debris‐flow terraces, bedrock strath terraces, and alluvial fan terraces are the significant aggradational landforms observed within the valley. They provide signatures of tectonic activity and past climatic records. We have analysed various geomorphic indices, namely, stream‐gradient index ( SL ), steepness index ( Ks ), hypsometric curve and index ( HI ), and asymmetric factor ( AF ) to map the spatial variability in tectonic processes across the major thrusts. The channel morphology (depth and width) of a river becomes adjusted in geological time because of long‐term tectonic and erosional processes. However, the channel geometry and deviations can be highly adjustable in a tectonically disturbed mountainous region. The deviations along the river course can be attributed to active tectonic movement along thrusts/faults or because of erosion/sedimentation processes. We applied a novel method called the river Gradient Length Anomaly (GLA) for 37 subbasins of the Kali River to deduce active deformation (uplift/subsidence) corresponding to the increased sedimentation and erosional rates, both from the upstream and downstream parts of the thrusted blocks, from where river flows through. The results of basin‐wise morphometric indices were corroborated with GLA anomaly and field observations, which suggests that the area has undergone active deformation between the Main Central Thrust (MCT) and Himalayan Frontal Thrust (HFT), which is attributed to the regional compression. The results of geomorphic and morphometric data are validated with the focal mechanisms of moderate earthquakes. The geomorphic analysis suggests that the hinterland part of eastern Kumaun is more active than the foreland region.